3D kinematic in freestyle cross country skiing (XCS) technique during world championships (Val di Fiemme 2013) - Canclini, Ar.; Canclini, An.; Baroni, G.; Pozzo, R. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: A free skiing race challenges the athletes to master a wide range of speeds and slopes and to adapt their technique accordingly. Indeed, skiers possess different skiing techniques and continuously change among them during a race. The skating technique has five predominant subtechniques, known as gears (G1-5) as suggested by Nilsson et al. 2004 (G2, G3 and G4 replace the old names V1-V2 and V2alternate). In the '90s several studies have been conducted in attempt to describe the most relevant aspects of XCS freestyle, but the kinematic information is generally limited in the velocity range. More recently Kvamme (2005), Smith (2007), Lindinger (2010), Stöggl (2010), Andersson (2010) compared biomechanical characteristics of the main skating techniques. In this work we collected and analyzed the 3D kinematics of the G2 gear in freestyle XCS performed by elite skiers engaged in recent a World Championships race. G2 is an asymmetrical uphill technique involving one poling action over every second leg stroke.